Childhood roles in the family, shame, and adult narcissism - Kaboğlu, Zeynep (İstanbul Bilgi Üniversitesi, 2020)
ABSTRACT: While some theoreticians believed that narcissism is a healthy and ordinary developmental stage, others argued that it is a pathological condition that resulted from the disturbances in early relationships. Narcissism is essentially related to a deficient sense of self and an intense need for validation. It is categorized into vulnerable narcissism and grandiose narcissism. Vulnerable narcissists are described as anxious and sensitive individuals, and grandiose narcissists are characterized as people who deny any weakness and aim to feel superior. Both types of narcissism are closely associated with the affect of shame that is derived from the failure at satisfying the perfectionist demands of the ego ideal. The nature of early parental relationships plays a critical part in establishing these exhausting ideals. Various kinds of roles that are taken in the family have a significant effect on an individual’s sense of self and his/her later life. Parentification is described as a phenomenon where children undertake parental roles that are inappropriate for their capabilities due to the lack of healthy boundaries in the family. Even though all these concepts are exemplified in clinical observations, there has been limited empirical research on narcissism, childhood roles and parentification, especially in the Turkish population. This study aimed to investigate the relationship between parentification, childhood roles, shame, and both types of narcissism without any specific hypotheses. A Perceived Role in the Family Scale (PRFS) was developed by researchers and used to examine how people defined their roles in the family in childhood. An online survey was conducted for the research, and results from 546 participants over the age of 18 were analyzed. The results showed that gender, the Mascot role and the Mediator role were predictors of grandiose narcissism in adults. The findings were discussed for their theoretical and clinical implications. Limitations of the study and suggestions for future research were presented.

ÖZET: Bazı kuramcılar narsisizmin bireyin sağlıklı ve normal gelişiminde yer alan bir evre olduğunu savunurken, bazıları gelişim dönemindeki sorunlar nedeniyle ortaya çıkan patolojik bir durum olduğunu iddia etmiştir. Narsisizm temel olarak yoğun bir onaylanma ihtiyacı ve problemli bir benlik algısı ile ilgilidir. Literatürde kırılgan narsisizm ve büyüklenmeci narsisizm olmak üzere iki kategori belirtilmiştir. Kırılgan narsisistler endişeli ve hassas, büyüklenmeci narsisistler ise zayıflığı inkar eden ve üstünlük edinmeyi amaçlayan kişiler olarak tanımlanmıştır. İki tip narsisizmin de ego idealindeki mükemmeliyetçi beklentilere ulaşamamanın yarattığı utanç duygusu ile yakından ilişkili olduğu düşünülmektedir. Aile içerisindeki ilişkiler özellikle erken gelişimsel dönemde bu zorlayıcı ideallerin oluşmasında etkilidir. Ailede oynanan rollerin, bireylerin benlik algısına ve hayatlarının geri kalanına etkisi olduğu düşünülmektedir. Ebeveynleşme, ailedeki sınır eksikliği sonucu, çocukların kapasitelerine uygun olmayan rol ve sorumlulukları üstlenmesi olarak açıklanmaktadır. Bu olgular klinik anlatımda sıklıkla yer alsa da özellikle Türkiye’de narsisizm, aile içindeki roller ve ebeveynleşme üzerine kısıtlı sayıda araştırma bulunmaktadır. Bu çalışma spesifik bir hipotez olmadan, ebeveynleşme, roller ve utanç duygusunun, kırılgan ve büyüklenmeci narsisizm ile ilişkisini araştırmayı hedeflemiştir. Bireylerin aile içindeki rollerini nasıl tanımladıklarını ölçmeye yönelik Kişinin Ailedeki Rolü Ölçeği geliştirilmiştir. Araştırma internet üzerinden bir anket ile yürütülmüş ve 18 yaşın üzerindeki 546 kişinin sonuçları analiz edilmiştir. Cinsiyetin, Maskot rolünün ve Ara Bulucu/Psikolog rolünün yetişkinlikte büyüklenmeci narsisizmin göstergesi olduğu bulunmuştur. Bulgular teorik ve klinik açıdan tartışılmıştır. Çalışmanın katkıları ve zayıf yanları belirtilmiş, ardından gelecek araştırmalar için öneriler sunulmuştur.
Çocuklukta ailede üstlenilen roller, utanç ve yetişkinlikte narsisizm
Keywords: narcissism; grandiose narcissism; shame; childhood roles; parentification; narsisizm; büyüklenmeci narsisizm; utanç; çocukluktaki roller; ebeveynleşme